The Influence of Work Stress and Workload on Work Motivation and Its Impact on the Performance of Class II Land Transportation Management Center Employees in South Sumatra - Riduan, M; Helmi, Sulaiman; Gunarto, Muji; Trisninawati, Trisninawati (International Journal of Finance Research, 2024)
This study provides valuable insights into the impact of work stress and workload on work motivation and subsequent employee performance at the Class II Land Transportation Management Center in South Sumatra. Employing a quantitative approach with a descriptive research design, the survey method is used to collect data, aligning with the positivist philosophy. Data is gathered through a structured questionnaire administered at the Office of Class II South Sumatra Land Transportation Management Hall from January to February. Results reveal a negative influence of work stress and workload on employee performance, although work motivation shows no significant correlation. Nevertheless, work motivation positively affects employee performance, independent of work stress and workload. These findings have practical implications for improving workplace conditions and enhancing employee productivity and job satisfaction. Recommendations for future research include further exploration of potential mediating factors, in-depth investigations into strategies for reducing work stress and workload, longitudinal studies to track changes in work motivation and performance, and comparative analyses with similar offices to gain insights into transportation sector dynamics